Seventh annual Voice of Portugal convention - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of attendees of the 7th annual Voice of Portugal convention. Men, women and children are wearing ribbons. A man holds up what appears to be an empty milk bottle.